Data and scholarly publishing: the transforming landscape. Issue 5 (1st September 2014) - MURPHY, Fiona
ABSTRACT: This article sets the scene for the special issue on research data and publishing. Research data – that material commonly accepted by the scholarly community as required evidence for hypotheses and insights, for verification and/or reproducibility of experiments – has become an increasingly critical issue for publishers given recent developments in funders' mandates, technological advances, policymakers' interests, and so forth. I outline some of the recent initiatives that are responding to policy directives, particularly Project ODE, and consider how publishers are working with data and integrating their practices with other collaborative efforts. A summary of the new policies, products, and partnerships demonstrates that the onus is now with scholarly publishers to gain an understanding of these developments and how they are affecting fellow key stakeholders within the research communications ecosystem.